PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIVEMENT DIVISIONS (STAD) DAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS ANEKDOT PADA SISWA KELAS X SMA NEGERI 6 KABUPATEN TANGERANG - Pabean, Galan Yutri; Tatu Hilaliyah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2026)
This study aims to analyze the effect of the implementation of the Student Teams Achievement Divisions (STAD) Learning Model, the influence of the Discovery Learning Model, and the difference in influence between the Student Teams Achievement Divisions (STAD) Learning Model and the Discovery Learning Model on the skills of writing anecdotal texts in class X of SMA Negeri 6 Tangerang Regency. This study uses a quantitative method with a Pretest-Posttest Control Group Design research design. The sample was taken using the random sampling method. The data analysis technique used the t-test with the help of the SPSS 29 program. Hypothesis testing used the t-test. The results of the t-test showed significance in the Student Teams Achievement Divisions (STAD) Learning Model and the Discovery Learning Model of 0.000 <0.005 so that Ha was accepted and Ho was rejected.